Hitting the Curveballs : How Crisis Can Strengthen and Grow Your Business - Myers, Jay (Morgan James Publishing, 2013)
In Hitting the Curveballs, small business owner Jay Myers coaches entrepreneurs to use crises to grow their business by inspiring them to embrace new strategies, including creative employee recruiting methods, niche marketing, using your book as a hook, and much more. Myers tells the story of how he led his own company to more than double its sales to $25 million from 2007 to 2011, when they lost 80% of their sales team and faced the worst economy in living memory. Buy this book if you want the encouraging voice of an experienced hitter behind you next time you step up to the plate.